Non-Invasive Prenatal Testing with Next Generation Sequencing Methods in Birth Defect Pregnancy: A Pilot Study - Anom Suardika; Anak Agung Ngurah Jaya Kusuma; Ni Gusti Ayu Manik Ermayanti; Endang Sri Widiyanti; I Gusti Ngurah Agung Satria Wibawa; Divika Silvana; Anak Agung Gede Raka Budayasa; Ni Nyoman Ayu Dewi; I Made Jawi; H. Sunny Sun; Yen-An Tang (Indonesian Biomedical Journal)
BACKGROUND: Identification of cell-free foetal DNA (cffDNA) in maternal blood, combined with next-generation sequencing (NGS) advancement, has paved the way for non-invasive prenatal screening to detect foetal aneuploidies. However, there is limited evidence on its diagnostic accuracy when compared with gold-standard invasive tests specifically in pregnancies complicated by birth defects in Indonesia. This study was conducted to evaluate the precision of non-invasive prenatal testing (NIPT) using NGS and ultrasound findings compared with the established benchmarks of amniocentesis and neonatal karyotyping through G-banding analysis, which is an invasive procedures, in a private laboratory setting for pregnancies with birth defect.